Navigating the infodemic through social media: A qualitative case study of Filipino university students’ learning experiences during the COVID-19 polycrisis - Janel Talaman; Mc Denver Necosia; Larence Villalon; Edrian Mark Tomines (Journal of Artificial Intelligence in Education & Learning Innovation, 2026)
Background: The COVID-19 pandemic has triggered a complex crisis in higher education that has not only disrupted formal learning but also given rise to an infodemic through the rapid spread of misinformation on digital platforms, making social media both a source of learning and a source of epistemic risk for students. Objectives: This study aims to explore how Filipino university students navigated learning experiences through social media during the COVID-19 polycrisis, focusing on preferred platforms, perceived educational relevance, and strategies for evaluating information credibility amid an infodemic. Methods: A qualitative case study design was employed. Six Filipino university students enrolled in a Bachelor of Elementary Education program participated in this study through purposive sampling. Data were collected via online semi-structured interviews, group chat discussions, document analysis of shared social media content, and follow-up interviews. Thematic analysis was conducted following Braun and Clarke's framework to identify recurring patterns across data sources. Results: Findings reveal that social media—particularly Facebook—served as a supplementary learning space, enabling students to access real-time information, engage with societal issues, and sustain their learning during the suspension of formal instruction. Students demonstrated active information-seeking behaviors, including cross-checking sources and exercising caution in sharing content. However, persistent exposure to misinformation highlighted their vulnerability within infodemic environments, especially in the absence of structured institutional guidance. Conclusions: Social media can support authentic and socially relevant learning during educational disruption, but its pedagogical value depends on students' critical and digital literacy capacities.